ANALYZING STUDENTS’ DIFFICULTIES TOWARD LISTENING COMPREHENSION - Darti ,; Andi Asmawati (ETERNAL (English, Teaching, Learning and Research Journal), 2017)
The study aims at finding the problems encountered by the students in listening comprehension.  Descriptive method was used to analyze and to find the solution about the problems. The research was conducted in State Islamic University of Alauddin Makassar. The population of this study was second semester students of English Education Department of Tarbiyah and Teacher training Faculty Academic year 2016/2017. There were 37 students as the subject in this study.  Data were gathered by questionnaire and interview while observation during listening was used to confirm students’ answer. The result of analyzing students’ difficulties toward listening comprehension showed that listening is very difficult skill for students who study foreign language. It was based on three factors influencing their listening; they were listening material, listener factor, and physical setting. Therefore, accents, pronunciation, speed of speech, insufficient vocabulary, different accent of the speakers, lack of concentration, and bad quality of recording were the major problems encountered by students’ English Education Department. Understanding students’ difficulties enable the lecturer to help the students developing the effective learning strategies and ultimately improve their listening. Solutions to overcome the problems were:  the teacher should adapt and improve listening material, activate students’ vocabulary, give the students variety of accent while practice listening in language laboratory, improve their pronunciation by training from native speakers, building students’ knowledge about the topic, give some strategy in listening, and always motivate students. The solutions were made as a suggestion for the lecturers.